2023
DOI: 10.1186/s12967-023-04370-6
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis in tumors and its relationship to other programmed cell death: role of non-coding RNAs

Abstract: Programmed cell death (PCD) plays an important role in many aspects of individual development, maintenance of body homeostasis and pathological processes. Ferroptosis is a novel form of PCD characterized by the accumulation of iron-dependent lipid peroxides resulting in lethal cell damage. It contributes to tumor progression in an apoptosis-independent manner. In recent years, an increasing number of non-coding RNAs (ncRNAs) have been demonstrated to mediate the biological process of ferroptosis, hence impacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 176 publications
0
4
0
Order By: Relevance
“…Our previous study demonstrated a critical role of CD71, becoming part of an aberrant gene/protein expression pattern upon neoplastic transformation and malignant progression of ATC, which strongly candidate it as potential direct or indirect therapeutic target [ 40 ]. In particular, the core of its therapeutic potential could be also the close relationship with iron-depending cell death [ 56 ]. For instance, CD71 is mainly involved in iron homeostasis, binding serum transferrin and thus contributing to the increase of the small pool of Fe 2+ (referred to as the labile iron pool), able to generate ROS, which in turn initiate lipid peroxidation and eventually lead to ferroptosis [ 15 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated a critical role of CD71, becoming part of an aberrant gene/protein expression pattern upon neoplastic transformation and malignant progression of ATC, which strongly candidate it as potential direct or indirect therapeutic target [ 40 ]. In particular, the core of its therapeutic potential could be also the close relationship with iron-depending cell death [ 56 ]. For instance, CD71 is mainly involved in iron homeostasis, binding serum transferrin and thus contributing to the increase of the small pool of Fe 2+ (referred to as the labile iron pool), able to generate ROS, which in turn initiate lipid peroxidation and eventually lead to ferroptosis [ 15 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, given the extraordinary complexity and heterogeneity of this group of disorders, sensitivity to ferroptosis may vary greatly among different types of cancer cells. For example, p53, which exerts a critical role in inhibiting tumorigenesis and other cancer processes such as invasion, metastasis, and metabolism, has been reported to control ferroptosis-related genes to prevent tumor growth [ 63 , 64 ]. However, as discussed in detail in Section 4.6 it recently emerged that p53 has opposing effects on ferroptosis regulation in different tumor cells.…”
Section: Ferroptosis As a Biological Program: Features And General Me...mentioning
confidence: 99%
“…With the advancement of cancer biology research, the interaction between programmed cell death (PCD) and malignant tumors has received widespread attention, being considered a crucial component in the occurrence of malignant tumors ( 9 , 10 ). As research progresses, an increasing number of researchers are focusing on the correlation between PCD and osteosarcoma occurrence ( 11 ).…”
Section: Introductionmentioning
confidence: 99%